ON THE EDGE-BALANCED INDEX SETS OF PRODUCT GRAPHS - Elliot Krop; Sin-Min Lee; Christopher Raridan (IndoMS, 2011)
We characterize strongly edge regular product graphs and find the edge-balanced index sets of complete bipartite graphs without a perfect matching, the direct product Kn X K2. We also prove a lemma that is helpful to determine theedge-balanced index sets of regular graphs.DOI : http://dx.doi.org/10.22342/jims.0.0.20.71-78